The Influence Of Climatic And Geographical Factors On The Development Of Arterial Hypertension In The Fergana Valley (Texas Journal of Medical Science, 2026)
Arterial hypertension (HTN) remains one of the leading causes of cardiovascular disease worldwide. Climatic and geographical conditions influence the course of the disease, exacerbating or mitigating its clinical manifestations. In the Fergana Valley (continental climate, hot, dry summers, and moderately cold winters), the prevalence and severity of hypertension may vary depending on temperature and environmental factors. This study aims to examine the relationship between climatic and geographical conditions and hypertension in the adult population of the region